how to factorise x2 + 5x +6
Answers
Answered by
1
ANSWER:-
EXPLANATION:-
![x ^{2} + 5x + 6 x ^{2} + 5x + 6](https://tex.z-dn.net/?f=x+%5E%7B2%7D++%2B+5x+%2B+6)
AFTER MIDDLE TERM SPLITTING..
![= {x}^{2} + 3 x + 2x + 6 = {x}^{2} + 3 x + 2x + 6](https://tex.z-dn.net/?f=+%3D++%7Bx%7D%5E%7B2%7D++%2B+3+x+%2B+2x+%2B+6)
NOW TAKE COMMON FROM THE FIRST TWO AND LAST TWO...
![= x(x + 3) + 2(x + 3) = x(x + 3) + 2(x + 3)](https://tex.z-dn.net/?f=+%3D+x%28x+%2B+3%29+%2B+2%28x+%2B+3%29)
NOW ,
![= (x + 3)(x + 2) = (x + 3)(x + 2)](https://tex.z-dn.net/?f=+%3D+%28x+%2B+3%29%28x+%2B+2%29)
HOPE IT HELPS....
EXPLANATION:-
AFTER MIDDLE TERM SPLITTING..
NOW TAKE COMMON FROM THE FIRST TWO AND LAST TWO...
NOW ,
HOPE IT HELPS....
Similar questions